2021
DOI: 10.1016/j.appet.2020.105005
|View full text |Cite
|
Sign up to set email alerts
|

Food choice motives and the nutritional quality of diet during the COVID-19 lockdown in France

Abstract: To limit the transmission of COVID-19, nationwide lockdown was imposed in France between March, 17th and May 10th, 2020. This disruption in individuals’ daily routines likely altered food consumption habits. We examined how changes in food choice motives related to changes in nutritional quality during the lockdown compared to before. A convenience sample of 938 French adults completed online questionnaires on the Qualtrics platform at the end of April 2020. Participants were retrospectively asked about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
197
3
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(279 citation statements)
references
References 33 publications
(33 reference statements)
24
197
3
19
Order By: Relevance
“…Variations in mental health may contribute to or impair healthy eating, in a bi-directional relation between eating and mental health: one’s mood or psychological state can affect what and how much one eats and eating affects one’s mood and psychological well-being [ 74 ]. A recent study revealed the importance of mood as the leading food choice motive in 48% of 938 adults interviewed about their food consumption during the COVID-19 lockdown in France [ 75 ]. This is in line with the results of our study: all mood changes in both parents and children were associated with a modification in children’s food consumption, either higher or lower; mood changes in children were mainly associated with weight gain, but also with weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in mental health may contribute to or impair healthy eating, in a bi-directional relation between eating and mental health: one’s mood or psychological state can affect what and how much one eats and eating affects one’s mood and psychological well-being [ 74 ]. A recent study revealed the importance of mood as the leading food choice motive in 48% of 938 adults interviewed about their food consumption during the COVID-19 lockdown in France [ 75 ]. This is in line with the results of our study: all mood changes in both parents and children were associated with a modification in children’s food consumption, either higher or lower; mood changes in children were mainly associated with weight gain, but also with weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Di Renzo et al (2020) studied eating habits and lifestyles changes during the lockdown among the Italian population (aged between 12 and 86 years). Marty, de Lauzon, Labesse & Nicklaus (2021) studied how changes in French adults’ food choice motives were related to changes in nutritional quality during the lockdown compared to the period before the lockdown. Pietrobelli et al (2020) conducted a study in Italy on eating behavior with parents of children aged 6–18 years, but the sample was very small (N = 41) and the children all had obesity.…”
Section: Introductionmentioning
confidence: 99%
“…CD has the peculiarity of merely dietetic treatment, which could be impacted in different ways by the restrictive measures, possibly implying difficulties in the supply of gluten-free products [ 3 ] or avoiding eating out, known to be an occasion of potential contamination or transgression to the GFD [ 4 , 5 ]. Previous findings on the impact of the lockdown on dietary habits in the general population are controversial, with some studies reporting a decrease in nutritional quality of diet on average worldwide [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], while a recent survey showed an increased healthy eating during the pandemic, thanks to less eating out and increased cooking [ 13 ]. Therefore, we aimed to assess the impact of the restrictive measures on the adherence of Italian CD subjects to the gluten-free diet (GFD) and on the management of the disease during the lockdown, by a web-based survey.…”
Section: Introductionmentioning
confidence: 99%